Inside Damanhur : a hidden world [videorecording (DVD)] - Manzo, Massimiliano; Gunnarrson, Axelina; Calea, Celastrina (Dreamscape Media, 2025)
A hidden world lies in the Italian countryside. Citizens of Damanhur, one of the largest esoteric communities on Earth, live a distinct life to those on the outside.